Using Zmijewski Model in the Prediction of Financial Distress State-Owned Banking - Pandoyo Pandoyo; Cundo Harimurti; Mohammad Sofyan (Budapest International Research and Critics University, 2022)
State-owned banking has a negative outlook due to asset quality challenges and difficulties in increasing revenue without taking additional risks due to the challenges of business models and difficult external conditions. The study aims to predict the financial health of state-owned banks with the Zmijewski model. This research is an analysis of secondary data based on the balance sheet of state-owned banks, namely: Bank Rakyat Indonesia, Bank Negara Indonesia, Bank Mandiri, and Bank Tabungan Negara, for the period 2017-2021 for financial distress predictions as measured by return on asset, debt ratio, and current ratio. Sampling method with saturated sampling. From the results of calculations with the Zmijewski model. It is known that the four state-owned banks are predicted to have financial difficulties and are at high risk of bankruptcy. Management must increase its current assets lest current debt exceeds the value of current assets owned. Increased liquidity in improving financial performance will improve the bank's performance.